Spiritual Burnout of Students: Diagnosis and Therapy in the Tradition of Islamic Boarding Schools - Fella Andari; Nindya Faza; Havin Zarkasih; Muhammad Amiruddin (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2026)
Spiritual burnout among Islamic boarding school (pesantren) students has emerged as a significant issue amid the intensive demands of religious observances, academic responsibilities, and the disciplined lifestyle of pesantren education. This study aims to examine the phenomenon of spiritual burnout among santri, develop an integrative diagnostic framework that combines modern psychological perspectives with the Salaf pesantren tradition, and formulate contextual therapeutic strategies for its recovery. Employing a qualitative approach through library research, this study draws upon scholarly books, journal articles, and relevant literature on burnout, mental health, Sufism, and Islamic boarding school education. The collected data were analyzed using a descriptive-analytical method within an integrative conceptual framework. The findings reveal that spiritual burnout is characterized by diminished enthusiasm for worship, reduced spiritual concentration (khushu’), loss of existential meaning, declining learning motivation, and a tendency toward social withdrawal. Accurate diagnosis requires the integration of psychological indicators, such as emotional exhaustion and motivational decline, with spiritual indicators, including weakened hudhur al-qalb (presence of heart) and inconsistency in devotional practices. Effective therapeutic interventions include Sufi-based spiritual exercises, riyadhah, tazkiyat al-nafs, communal support within the pesantren environment, guidance from religious mentors, and selected modern psychological techniques. This study concludes that a holistic approach integrating psychology and the Pesantren tradition offers a comprehensive framework for diagnosing and addressing spiritual burnout while fostering the mental and spiritual well-being of santri.